Icono: a universal language that shows what it says - Kramer, Peter (Frontiers in Psychology, 2023)
This article lays out the foundation of a new language for easier written communication that is inherently reader-friendly and inherently international. Words usually consist of strings of sounds or squiggles whose meanings are merely a convention. In Icono, instead, to aid their recall, they typically are strings of icons that illustrate what they stand for. “Train”, for example, is expressed with the icon of a train, “future” with the icon of a clock surrounded by a clockwise arrow, and “mammal” with the icons of a cow and a mouse—their combination’s meaning given by what they have in common. On smartphones and computers, writing icons can now be faster than writing alphabetic words. And using simple pictures as words helps those who struggle with conditions like dyslexia, aphasia, cerebral palsy, and autism with speech impairment. Moreover, to aid parsing, Icono also reveals sentence structure graphically before, rather than linguistically after, one begins reading. Because it shows what it says, Icono is bound to be easier to learn to read—and subsequently easier to read—than any other language, including our own.